On certainty and other philosophical essays on cognition. - Rescher, Nicholas (Berlin : De Gruyter, 2011)
On Certainty continues Rescher's longstanding practice of publishing occasional studies that form part of a wider program of investigation of the scope and limits of rational inquiry in the pursuit of understanding. And pragmatism forms a subtextual Leitmotiv of these essays, seeing that the linking idea at work throughout is that knowledge is a tool for the management of our theoretical and practical affairs, and that what we ask of it is serviceability for the uses we have in view.
Preface; Chapter One ON CERTAINTY; Chapter Two PRACTICAL INFERENCE IN THEORETICAL CONTEXTS; Chapter Three ON THE COMPLICATIONS OF EPISTEMIC QUALITY; Chapter Four PERSUASION; Chapter Five APORY; Chapter Six COGNITIVE OBLIGATION; Chapter Seven SEMANTICAL APPROXIMATION; Chapter Eight COGNITIVE REFLEXIVITY AND THE LIMITS OF KNOWLEDGE; Chapter Nine ISSUES OF ULTIMATE EXPLANATION; REFERENCES; Name Index.
Print version record.
Zahlr. Abb.
In English.
eBooks on EBSCOhost
Keywords: Cognition -- Philosophy; Cognition -- Philosophie; PHILOSOPHY -- Metaphysics; Cognition -- Philosophy